What does a “good life” mean for people living with dementia? A protocol for a think-aloud study informing the value of care - Kinchin, Irina; Leroi, Iracema; Kennelly, Sean P.; Kochovska, Slavica; Brady, Conor; Fitzhenry, Deborah; McHale, Cathy; Kinghorn, Philip; Coast, Joanna (Frontiers in Aging Neuroscience, 2022)
Introduction Economic evaluation currently focuses almost exclusively on the maximization of health, using the Quality-Adjusted Life-Year (QALY) framework with instruments such as the EQ-5D, with a limited number of health-focused dimensions providing the assessment of health benefit. This evaluative framework is likely to be insufficient for setting priorities in dementia care because of its exclusive concern with health. Data are also often collected from the perspective of a proxy, limiting the voice of those living with dementia in decision-making. This protocol describes a research project that aims to gather the perspectives of people living with dementia, their insights, and preferences for assessing their quality of life to inform economic evaluation outcome measurement and design with a goal of creating a more robust evidence base for the value of healthcare services. Specifically, this study will elucidate what a “good life” means to people living with dementia and how well instruments currently used in economic evaluation meet this description. This project will further test the acceptability of capability wellbeing instruments as self-report instruments and compare them to generic and dementia-specific preference-based instruments. Methods and analysis People living with dementia, diagnosed, or waiting to receive a formal diagnosis and with the capacity to participate in research, will be invited to participate in an hour “think aloud” interview. Participants will be purposefully selected to cover a range of dementia diagnoses, age, and sex, recruited through the integrated care, geriatric, and post-diagnostic clinics at St James’ and Tallaght University Hospitals and dementia support groups in the Ireland. During the interview, participants will be invited to reflect on a “good life” and “think aloud” while completing four economic quality of life instruments with a perspective that goes beyond health (AD-5D/QOL-AD, AQOL-4D, ICECAP-O, ICECAP-SCM). An interviewer will then probe areas of difficulty when completing the instruments in a semi-structured way. The analysis will identify the frequency of errors in comprehension, retrieval, judgment, and response from verbatim transcripts. Qualitative data will be analyzed using constant comparison. Ethics The St James’s Hospital and Tallaght University Hospital Joint Research Ethics Committee approved the study (Approval Date: 11 April 2022).